Answer:
(a) - 4.9 x 10^6 m/s
(b) - 4.38 x 10^6 m/s
(c) 17.36 x 10^-14 J
Step-by-step explanation:
M = 1.58 x 10^-26 kg
U = 0
m1 = 5.04 x 10^-27 kg
v1 = 6 x 10^6 m/s along Y axis
m2 = 8.5 x 10^-27 kg
v2 = 4 x 10^6 m/s along X axis
Let m3 be the mass of third particle which is moving with velocity v having X axis component is vx and y axis component is vy.
So, m3 = M - m1 - m2 = 1.58 x 10^-26 - 5.04 x 10^-27 - 8.5 x 10^-27
m3 = 6.9 x 10^-27 kg
(a) Use the conservation of momentum along X axis
M x U = m1 x 0 + m2 x v2 + m3 x vx
0 = 0 + 8.5 x 10^-27 x 4 x 10^6 + 6.9 x 10^-27 x vx
vx = - 4.9 x 10^6 m/s
(b) Use the conservation of momentum along Y axis
M x U = m1 x v1 + m2 x 0 + m3 x vy
0 = 5.04 x 10^-27 x 6 x 10^6 + 0 + 6.9 x 10^-27 x vy
vy = - 4.38 x 10^6 m/s
(c) The resultant velocity of third mass,
The formula for the kinetic energy is
Total kinetic energy =
K = 17.36 x 10^-14 J